Penegakan Hukum Pencucian Uang Cryptocurrency sebagai Revolusi Kejahatan Masa Digital - Irlanda, Febrina (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 13 No 4 (2024), 2025)
This study analyzes the regulation and enforcement of cryptocurrency-related money laundering in Indonesia compared to the United States. Through normative legal research method and a comparative approach, regulations in both countries are evaluated. In the United States, government agencies such as FinCEN, IRS, and SEC play roles in law enforcement, while Indonesia relies on BAPPEBTI. Although the United States has more comprehensive laws, Indonesia has also taken steps to address this issue, including through the "Travel Rule." However, the main challenge is the anonymity of cryptocurrency, which makes investigations difficult. To address this, more detailed regulations are needed, along with international cooperation to prevent money laundering through cryptocurrency.